Remote sensing and GIS in disasters management-in special reference to Asian countries - Shrivastava, Rajesh (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> During the past five decades, natural hazards such as floods, earthquakes, severe storms and tropical cyclones, droughts, wild land fires, and also manmade disasters such as Nuclear disaster, oil spills, and terrorist attacks have caused major loss of human lives and livelihoods, the destruction of economic and social infrastructure, as well as environmental damages. Disaster reduction is both an issue for consideration in sustainable development agenda and a cross cutting issue relating to social, economic, environmental and humanitarian sectors. These important features have to analyze and there is a need to study. Though, in recent years the Open GIS technology standards have been developed by several agencies, which provide the basis for utilization of geographic information services, also gives an opportunity for data interoperability, data integration and data sharing between different emergency management agencies, However finding suitable services and visualization of geospatial information for decision makers is still a crucial task. Objective of this paper is to assess the state of art literature review in different methodologies of utilizing geospatial technology in managing both natural and manmade disasters dedicated by different authors and also to find new direction in this important area. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->